(untitled) (LEARNing Landscapes, 2018)
In 1982 Harvard University Press published Carol Gilligan’s landmark work, In a Different Voice, a book on psychological theory and women’s development, which sparked a heated discussion in the world of psychology. After listening to women speaking about themselves and about morality, Gilligan noticed that psychologists would study men and generalize to humans, and decided to explore the different voice she had heard. That became the basis of her book. In this interview she explains the origins of the book, how the book was received by the psychological community at the time, and why it had the impact that it did.